Reoperation for Late Neurological Deterioration After Laminoplasty in Individuals With Degenerative Cervical Myelopathy: Comparison of Cases of Cervical Spondylosis and Ossification of the Posterior Longitudinal Ligament. Issue 15 (1st August 2020) - Nakashima, Hiroaki; Kanemura, Tokumi; Satake, Kotaro; Ito, Kenyu; Ouchida, Jun; Morita, Daigo; Ando, Kei; Kobayashi, Kazuyoshi; Ishiguro, Naoki; Imagama, Shiro
Abstract : Study Design: Retrospective cohort study. Objective: The objective of this study was to elucidate the rate and causes of reoperation for late neurological deterioration after cervical laminoplasty by comparing cases of cervical spondylotic myelopathy (CSM) with those of ossification of the posterior longitudinal ligament (OPLL). Summary of Background Data: Although the long-term surgical outcomes of cervical laminoplasty in patients with CSM or OPLL are satisfactory, reoperation is sometimes required for late neurological deterioration after laminoplasty. However, limited information is available about long-term follow-up in such cases. Methods: This retrospective cohort study included 623 patients who underwent cervical laminoplasty for cervical myelopathy (average follow-up duration, 6.1 [range, 2–15] years). The rate of reoperations for late neurological deterioration (>6 mo after the initial surgery) was investigated. Results: Primary diagnoses were CSM and OPLL in 522 (83.8%) and 101 (16.2%) patients, respectively. During the follow-up period, 10 (1.6%) patients required reoperation: 7 (1.3%) in the CSM group and 3 (3.0%) in the OPLL group. No significant difference was found between the CSM and OPLL groups regarding patients requiring reoperation ( P  = 0.26). The mean elapsed time between primary surgery and reoperation was 4.7 ± 3.2 and 10.0 ± 5.7 years in the CSM and OPLL groups, respectively. The predicted risk percentages of reoperation at 10 years after primary surgery were 2.9% and 1.0% in the CSM and OPLL group, respectively. The causes of reoperation for CSM were C5 palsy in five, severe radiculopathy in one, and restenosis due to instability after laminoplasty in one case; the cause of reoperation for OPLL was enlargement of ossification in all three cases. Conclusion: Although the clinical outcomes of laminoplasty were favorable in most patients, reoperation for late neurological deterioration was required in approximately 1.0% to 3.0% of CSM and OPLL cases within 10 years after laminoplasty. Level of Evidence: 4 Abstract : Although the clinical outcomes of laminoplasty were favorable in most cases, 1.0% to 3.0% of patients with late neurological deterioration required reoperation within 10 years. The most common causes of reoperation were C5 palsy in cervical spondylotic myelopathy cases and enlargement of ossification in ossification of the posterior longitudinal ligament cases.